Pandas - Schreiber, Anne. (Washington, D.C. : National Geographic, 2010)
Photographs and text introduce readers to giant pandas, discussing how they look, what they eat, and where they live, looking at the lives of baby pandas, and explaining why pandas need to be protected.
3.3
K-3
K-3
Keywords: Pandas -- Juvenile literature; Pandas; Pandas; Readers (Elementary)